Peranan Kreativitas dan Inovasi Dalam Usaha Meningkatkan Volume Penjualan Pada Pondok ”Aroma Vegetarian - Rusdianto Rusdianto; Subiyanto Subiyanto; Arini Arini (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This research was conducted with the aim of describing the process of making food and drinks and serving food at the Palembang Aroma Vegetarian Pondok Restaurant located at Jalan Address. Lt. Abdul Rozak No. 62, Duku, Kec. Ilir Team. II, Palembang City. This study uses creativity and innovation of qualitative descriptive research in the form of exposure to data on the process of making and serving food menus at the Palembang Aroma Vegetarian Restaurant which were obtained from direct observation and secondary data from various sources. Collecting data using observational interviews and documentation of data analysis starting from descriptive qualitative. In the process of making and serving food at the Palembang vegetarian aroma cottage restaurant, the presentation of the food is very attractive and prepares a menu of Chinese food and Indonesian food equipped with fresh drinks. Pengumpulan data menggunakan wawancara observasi dan dokumentasi analisis data dimulai dari deskriptif kualitatif. Dalam proses pembuatan dan penyajian makanan resto pondok aroma vegetarian Palembang yang penyajian makanan nya sangat menarik serta menyiapkan menu makanan chinese dan makanan nusantara dilengkapi dengan minuman yang segar.